Implementation of Interactive Digital Media: A Case Study of Articulate Storyline in Indonesian Language Learning - Nisa, Khoirin; Ansori, Isa (Journal of Practice Learning and Educational Development, 2025)
The limited active participation of students in Indonesian language learning at the elementary school level remains a pedagogical challenge that has not been effectively addressed. Conventional teacher-centered practices tend to create passive learning environments and diminish students’ enthusiasm for learning. To address this issue, the present study aims to examine the effectiveness of the Articulate Storyline platform in enhancing fourth-grade elementary students’ engagement in Indonesian language learning. Employing a qualitative case study design, the research involved 25 students and one teacher from SDN Jekulo 02 Kudus. Data were collected through participant observation, in-depth interviews, and documentation, and were analyzed using the Miles and Huberman interactive model. The findings reveal that the implementation of Articulate Storyline significantly increased students’ activeness in asking questions (from 32% to 84%), participation in discussions (40% to 92%), concentration in learning (48% to 96%), and enthusiasm in completing assignments (36% to 88%). The media also facilitated spontaneous collaboration, independent learning, and the development of listening, speaking, reading, and writing skills. Its interactive and contextually relevant multimedia features proved to be the primary drivers of increased student motivation. Nevertheless, limitations in device availability and digital literacy emerged as technical barriers that need to be addressed. The study recommends the sustainable integration of interactive digital media, accompanied by teacher training and the development of adaptive local content, as a strategy for transforming Indonesian language learning in elementary schools.